Optimizing Drug-Resistant Tuberculosis Treatment Outcomes in a High HIV-Burden Setting: A Study of Sputum Conversion and Regimen Efficacy in Rural South Africa - Mojisola Clara Hosu; Lindiwe Modest Faye; Teke Apalata (Pathogens)
Background: Sputum culture and smear conversion are key indicators of treatment response in drug-resistant tuberculosis (DR-TB). This study aimed to assess sputum conversion and regimen efficacy among DR-TB patients and identify factors influencing conversion rates. Methods: This retrospective cohort study analyzed medical records of DR-TB patients treated between 2018 and 2020 in the Eastern Cape Province, South Africa. Kaplan–Meier curves, Spearman correlation, and logistic regression models were used to assess time-to-sputum conversion and its predictors. Results: Among the 88% of patients who achieved sputum conversion, the median time ranged from 29 to 59 days. Patients on short treatment regimens converted significantly faster than those on long regimens (p = 7.55 × 10−15), with 90% of short-regimen patients achieving favorable outcomes compared to 52% in the long regimen group (p = 0.0000040). Spearman correlation revealed a weak but significant positive association between comorbidities and conversion time (r = 0.041, p = 0.041). HIV-positive patients had a slower conversion rate than HIV-negative patients, but this association was not statistically significant (χ2 = 0.426, p = 0.514). Logistic regression identified older age as a predictor of favorable outcomes (coefficient = 0.039, p = 0.045), while regimen type and HIV status did not show significant predictive power. Conclusions: Shorter treatment regimens significantly improve sputum conversion rates and treatment outcomes. The findings support optimizing DR-TB treatment through personalized regimens based on patient health status and drug resistance patterns. This study provides evidence to enhance TB control efforts in high-burden regions, with implications for global treatment strategies.